A REVIEW ON THE HEAT-TRANSFER PERFORMANCE AND PRESSURE-DROP CHARACTERISTICS OF VARIOUS ENHANCED TUBES - Laohalertdecha, S.; Dalkilic, A. S.; Wongwises, S. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
The enhanced tube is a kind of the passive technique for improving the thermal performance of the heat exchangers with a little increase of the friction penalty. They have stated to use instead of the common smooth tubes for designing of the heat exchangers. The size of these heat exchangers can be reduced considerably by using the enhanced tubes instead of smooth tubes. Normally, they are divided into four groups: the corrugated tube, ribbed tube, grooved tube, and fluted tube. Compared with the common smooth tube, many researchers reported that use of the enhanced tubes dramatically increases the heat-transfer performance, both theoretically and experimentally. Focusing on the advantages of the enhanced tubes, this article summarizes the published studies on the heat-transfer and pressure-drop characteristics of the enhanced tubes, both experimental and quantitative investigations.
Keywords: Enhanced tubes; heat-transfer performance; pressure drop; heat exchanger; Thermodynamics